Pre-existing oncohematological disease in kidney transplant recipients: impact on graft survival, acute rejection, and long-term clinical outcomes - Mella, Alberto; Clari, Roberta; Deiana, Valeria; Giraudi, Roberta; Giovinazzo, Gloria; Gallo, Ester; Dolla, Caterina; Lavacca, Antonio; Manzione, Ana Maria; Fop, Fabrizio; Allesina, Anna; Cavallo, Federica; et al. (Frontiers in Immunology, 2025)
IntroductionOncohematological disorders are heterogeneous conditions that present significant challenges in management prior to transplantation. Data about rejection risk, disease recurrence, eligibility criteria, and requested remission time before kidney transplant (KT) are still lacking.MethodsAll KTRs between January 1, 2000, and March 31, 2023 (n = 2871) were analyzed. All patients with an oncohematological disease (hematological cohort, including plasma cell dyscrasias [PCDs], acute leukemia, high-grade lymphoma/post-transplant lymphoproliferative disorders [PTLDs], myeloproliferative neoplasms [MPNs], myelodysplastic/myeloproliferative neoplasms [MDS/MPNs], and genetic/AA amyloidosis) were matched 1:2 by age at transplant, gender, type of dialysis, and eGFR at transplant with KTRs without a history of hematological disease (control cohort). Primary endpoints were death-censored graft survival and the risk of rejection. Secondary endpoints included the risk of hematological disease recurrence and infection, patient survival rates, and graft function.ResultsThirty out of 2871 patients (1.04%) receiving 31/3019 KTs have a pre-existing oncohematological disease (hematological cohort): 7/30 (23.3%) PCDs, 4/30 (13.3%) acute leukemia, 8/30 (26.7%) high-grade lymphomas/PTLDs, 4/30 (13.3%) MPNs, 2/30 (6.7%) MDS/MPNs, and 5/30 (16.7%) AA/familiar amyloidosis. Patients were transplanted at a median time of 5 (PCDs), 11.8 (acute leukemia), 12.3 (high-grade lymphomas/PTLDs), 8.5 (MPNs), 3.6 (MDS/MPNs), and 3.5 years (amyloidosis) after achieving disease remission (or stable disease in smoldering myeloma, MPNs, and MDS/MPNs). Comparing hematological and control cohorts, no differences were observed in patient and graft survival or post-transplant complications, including acute rejections. Results are superimposable also without considering the three patients who underwent living KTs from the same donor as the bone marrow transplant. Hematological disease relapses were observed in 2/30 (6.6%), including a light-chain deposition and a Castleman disease, both of which were successfully treated with chemotherapy without allograft dysfunction.ConclusionsFavorable long-term transplant and clinical outcomes were achieved in patients with various pre-existing oncological and hematological disorders. These patients should not be denied KT after a well-documented stable disease. In this context, a multidisciplinary approach is crucial for establishing standardized pre- and post-transplant monitoring protocols and achieving optimal graft and patient outcomes.